Design and Analysis of an FTTH-GPON in a Residential Area - Rima Fitria Adiati; Apriani Kusumawardhani; Heru Setijono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
FTTH design is a crucial step to ensure the best performance of the optical link. In this paper, an FTTH-GPON network is designed, and its performance is analyzed using an optical link power and rise time budget. In the residence of 254 users, at least eight feeder cable cores are needed, with respective ODCs and ODPs. The design satisfies the link power budget with the lowest power margin of 2.469 dB/2.826 dB upstream/downstream in its furthest distance. The highest rise time for the system is 0,2236 nm. The FTTH configuration satisfies ITU-T G.984.1 GPON standard.